2020
DOI: 10.1002/pbc.28582
|View full text |Cite
|
Sign up to set email alerts
|

Race, ethnicity, and socioeconomic differences in incidence of pediatric embryonal tumors in the United States

Abstract: Background The etiology of childhood cancers and its social patterning remains largely unknown. Accounting for socioeconomic status (SES) when exploring the association between race/ethnicity and cancer incidence is necessary to better understand such etiology. We aimed to investigate differences in the incidence of embryonal tumors (ETs) by SES and race/ethnicity in the United States using population‐based registries of the Surveillance, Epidemiology, and End Results (SEER) Program. Procedure Children with ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(32 reference statements)
1
6
1
Order By: Relevance
“…By contrast, a recent analysis of racial and ethnic differences in embryonal tumor incidence suggested that these may be modified by socioeconomic status. 50 Finally, although we were not able to account for birth characteristics and other exposures that may be associated with race and ethnicity, our overall IRR estimates are similar to those reported previously. 3 Thus, it is likely that genetic variants contribute to the racial and ethnic differences risk of many cancers, but the degree to which differences are explained by genetics may vary by tumor type.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…By contrast, a recent analysis of racial and ethnic differences in embryonal tumor incidence suggested that these may be modified by socioeconomic status. 50 Finally, although we were not able to account for birth characteristics and other exposures that may be associated with race and ethnicity, our overall IRR estimates are similar to those reported previously. 3 Thus, it is likely that genetic variants contribute to the racial and ethnic differences risk of many cancers, but the degree to which differences are explained by genetics may vary by tumor type.…”
Section: Discussionsupporting
confidence: 73%
“…Although the incidence of acute lymphoblastic leukemia rose with increasing socioeconomic status among Black children, at all levels their rate was substantially lower than that in White children. By contrast, a recent analysis of racial and ethnic differences in embryonal tumor incidence suggested that these may be modified by socioeconomic status 50 . Finally, although we were not able to account for birth characteristics and other exposures that may be associated with race and ethnicity, our overall IRR estimates are similar to those reported previously 3 .…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies demonstrated that some minority groups have a higher risk of neuroblastoma. 7,8,20 may not accurately represent the risk susceptibility between different ancestries. 45,52 Further study is warranted to verify whether the effect size of GWAS SNPs differs between populations and whether there are ancestry-specific genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant associations, but we would be remiss if we did not mention the limitations of the data. Previous studies demonstrated that some minority groups have a higher risk of neuroblastoma 7,8,20 . Because the CI5 data do not break down populations by race/ethnicity, we used the limited information to categorize populations into predominant ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation